1999
DOI: 10.1074/jbc.274.30.21276
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures of Zinc-free and -bound Heme Domain of Human Inducible Nitric-oxide Synthase

Abstract: The crystal structures of the heme domain of human inducible nitric-oxide synthase (NOS-2) in zinc-free and -bound states have been solved. In the zinc-free structure, two symmetry-related cysteine residues form a disulfide bond. In the zinc-bound state, these same two cysteine residues form part of a zinc-tetrathiolate (ZnS 4 ) center indistinguishable from that observed in the endothelial isoform (NOS-3). As in NOS-3, ZnS 4 plays a key role in stabilizing intersubunit contacts and in maintaining the integrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
133
0
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(138 citation statements)
references
References 41 publications
3
133
0
2
Order By: Relevance
“…Dimerization of heme-containing iNOS monomers can be enhanced by the presence of BH 4 by hydrophilic interactions (15,16,24,25). In hepatocytes, BH 4 is expressed constitutively at levels sufficient for iNOS activity (10,26).…”
Section: Discussionmentioning
confidence: 99%
“…Dimerization of heme-containing iNOS monomers can be enhanced by the presence of BH 4 by hydrophilic interactions (15,16,24,25). In hepatocytes, BH 4 is expressed constitutively at levels sufficient for iNOS activity (10,26).…”
Section: Discussionmentioning
confidence: 99%
“…The dimeric form of iNOS oxygenase domain has been shown through crystallography studies to contain a lone zinc ion coordinated by four cysteine residues along the dimer interface; this structure has been suggested to contribute to the stability of the complex [46]. There was no indication, however, of the presence of zinc in any of the experiments; no adduct of zinc was ever observed, nor was zinc lost as an ion in any CID experiments.…”
Section: More Detailed Analysis Of the Inos Oxygenase Domainmentioning
confidence: 97%
“…Formation-The crystal structures of the eNOS and iNOS heme domain dimers revealed that L-Arg binds to the active site of the heme domain with hydrogen bonding to Glu-371 of mouse iNOS (Glu-361 in human eNOS, corresponding to Glu-592 in rat nNOS) (23)(24)(25)(26). The E592A mutation resulted in a loss of sensitivity to L-Arg, characterized by a lack of spectroscopic perturbation on its addition (Fig.…”
Section: Effect Of the E592a Mutation On Electron Transfer And Dimermentioning
confidence: 99%